Ten-Year Changes in Bloodstream Infection With Acinetobacter Baumannii Complex in Intensive Care Units in Eastern China: A Retrospective Cohort Study - Meng, Xiao; Fu, Jintao; Zheng, Yue; Qin, Weidong; Yang, Hongna; Cao, Dongming; Lu, Haining; Zhang, Lu; Du, Zhiguo; Pang, Jiaojiao; Li, Wei; Guo, Haipeng; et al. (Frontiers in Medicine, 2021)
Background: There is little evidence on the changing prevalence, microbiological profile, and outcome of nosocomial Acinetobacter baumannii complex (ABC)-caused bloodstream infection (ABCBSI) specified in intensive care units (ICUs) in long-term studies, especially in China. Objective: We aimed to investigate changes in incidence, antibiotic resistance, therapy, and prognosis of ABCBSI in ICUs in eastern China during 2009–2018. Methods: A multicenter retrospective cohort study was conducted, and microbiological and clinical data for patients with ABCBSI acquired in nine adult ICUs in eastern China from 2009 to 2018. Results: A total of 202 cases were enrolled. For the years 2009–2010, 2011–2012, 2013–2014, 2015–2016, and 2017–2018, the incidence of ABCBSI increased significantly, as did the percentage of pan-drug-resistant isolates and resistant rates to most of antimicrobial agents; the percentage of drug-sensitive isolates decreased (all P < 0.05). The frequency of treatment with carbapenems and tigecycline increased, and that of cephalosporins decreased. Compared with those in the first years (2009–2012), ABCBSI patients in the lattermost years (2017–2018) were less often treated with appropriate empirical therapy, more often underwent pneumonia-related ABCBSI and mechanical ventilation support, and had higher 28-day mortality rates. Multivariate Cox regression indicated that increase in the degree of ABC antibiotics resistance, pneumonia-related ABCBSI, and septic shock were risk factors of 28-day mortality and associated with significant lower survival days. Conclusions: The past decade has witnessed a marked increase in the incidence of ABCBSI and in antibiotic resistance, with increasing pneumonia-related infections and worrisome mortality in ICUs in China. Controlling increasing resistance and preventing nosocomial pneumonia may play important roles in combatting these infections.